FAKTOR-FAKTOR YANG MEMPENGARUHI KONSUMEN MEMBELI SEPATU CONVERSE PALSU PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS SYIAH KUALA - Chikita Divariyana, Ahmad Nizam (Departemen Manajemen, 2018)
Abstract :This study aims to determine the factors that affect consumers to buy fake converse shoes consisting of value consciousness, social status, low prices, and past experience of purchasing fake converse shoes on students faculty of economics and business of Syiah Kuala University . The sample used in this research is the on students faculty of economics and business of Syiah Kuala University who have used converse shoes with price below Rp.500.000.,-. This research method using questionnaire as research instrument. Non probability sampling is used as a sampling technique. Methods of testing analysis and data analysis were done using SPSS (Statistic Package for Social Science) version 20 with the formulation of multiple regression. The results of this study indicate that value consciousness does not affect the purchase of fake converse shoes, Social status affects the purchase of fake converse shoes, Low prices affect the purchase of fake converse shoes, and past experiences affect the purchase of fake converse shoes.Keywords:Value Conscoiusness, Social Status, Low Price, Past Experience, Purchase of Fake Converse Shoes